The Characteristics of Organic Carbon in the Offshore Sediments Surrounding the Leizhou Peninsula, China - Xia, Jia; Han, Yongqiang; Tan, Jingqian; Abarike, Grace Awinmalsim; Song, Zhiguang (Frontiers in Earth Science, 2022)
A total of 43 seafloor surface sediment samples collected from the offshore region surrounding the Leizhou Peninsula were analyzed in terms of the total organic carbon content (TOC), total nitrogen (TN), organic carbon isotope (δ13Corg) and sediment grain size. Our results showed that the organic carbon content in the samples ranged from 0.12% to 0.79%, with an average of 0.42% which was lower compared with other offshore regions of China, whereas the δ13Corg was in the range of -22.47‰ to -19.18‰. The total nitrogen content ranged from 0.011% to 0.100% which was also low. The combination of δ13Corg and TOC/TN ratio (5.1 to 14.3) suggested that the organic matter is dominant by marine authigenic source input, as marine sourced organic matter accounts for 71%, 82% and 75% in the sediments from the offshore areas of the east side, west side and the south (Qiongzhou Strait) of the Leizhou Peninsula, respectively. The weak/poor correlations between the organic carbon and clay, silt content, the pH and Eh value suggested that organic matter abundance and distribution were influenced by the source input of organic matter, the seafloor sediments’ redox status, and seawater’s hydrodynamic condition.